Phylogenetic conservation of freshwater lake habitat preference varies between abundant bacterioplankton phyla. (18th January 2016) - Schmidt, Marian L.; White, Jeffrey D.; Denef, Vincent J.
Summary: Despite their homogeneous appearance, aquatic systems harbour heterogeneous habitats resulting from nutrient gradients, suspended particulate matter and stratification. Recent reports suggest phylogenetically conserved habitat preferences among bacterioplankton, particularly for particle‐associated (PA) and free‐living (FL) habitats. Here, we show that independent of lake nutrient level and layer, PA and FL abundance‐weighted bacterial community composition (BCC) differed and that inter‐lake BCC varied more for PA than for FL fractions. In low‐nutrient lakes, BCC differences between PA and FL fractions were larger than those between lake layers. The reverse was true for high‐nutrient lakes. Nutrient level affected BCC more in hypolimnia than in epilimnia, likely due to hypolimnetic hypoxia in high‐nutrient lakes. In line with previous reports, we observed within‐phylum operational taxonomic unit (OTU) habitat preference conservation, although not for all phyla, including the phylum with the highest average relative abundance across all habitats ( B acteroidetes ). Consistent phylum‐level habitat preferences may indicate that the functional traits that underpin ecological adaptation of freshwater bacteria to lake habitats can be phylogenetically conserved, although the levels of conservation are phylum dependent. Resolving taxa preferences for freshwater habitats sets the stage for identification of traits that underpin habitat specialization and associated functional traits that influence differences in biogeochemical cycling across freshwater lake habitats.